Value of witness observations in the differential diagnosis of transient loss of consciousness. (26th February 2019) - Chen, Min; Jamnadas-Khoda, Jenny; Broadhurst, Mark; Wall, Melanie; Grünewald, Richard; Howell, Stephen J.L.; Koepp, Matthias; Parry, Steve W.; Sisodiya, Sanjay M.; Walker, Matthew; Hesdorffer, Dale; Reuber, Markus
Abstract : Objective: This retrospective study explores to what extent additional information from event witnesses provided using the novel 31-item Paroxysmal Event Observer (PEO) Questionnaire improves the differentiation among epilepsy, syncope, and psychogenic nonepileptic seizures (PNES) achievable with information provided by patients alone. Methods: Patients with transient loss of consciousness caused by proven epilepsy (n = 86), syncope (n = 79), or PNES (n = 84) attending specialist neurology/syncope services in the United Kingdom and event observers provided Paroxysmal Event Profile (PEP), PEO, and personal information (PI) (e.g., sex, age, medical history) data. PEO data were subjected to exploratory factor analysis (EFA) followed by confirmatory factor analysis (CFA). PEO, PEP, and PI data were used separately and in combination to differentiate diagnoses by pairwise and multinomial logistic regressions. Predicted diagnoses were compared with gold standard medical diagnoses. Results: EFA/CFA identified a 4-factor structure of the PEO based on 26/31 questionnaire items with loadings ≥0.4. Observer-reported factors alone differentiated better between syncope and epilepsy than patient-reported factors (accuracy: 96% vs 85%, p = 0.0004). Observer-reported data improved accuracy over differentiation based on patient-reported data alone from 90% to 100% between syncope and epilepsy ( p = 0.005), 76% to 83% between epilepsy and PNES ( p = 0.006), and 93% to 95% between syncope and PNES ( p = 0.098). Conclusions: Information from observers can make an important contribution to the differentiation of epilepsy from syncope or PNES but adds less to that of syncope from PNES.